Control de táreas escolares a domicilio para alumnos del segundo al séptimo año de educación básica dirigida por un grupo selecto y capacitado de estudiantes universitaríos de la ciudad de Guayaquil - Romero Aguilar, Diana Carolina (2009)
Our project is focused on determining whether school performance that is currently seen in classrooms is appropriate for the students’ optimal learning. As a consequence of this need, arises the idea of business, which aims to provide the service that allows improving the school performance, achieving in this way, parents more satisfied with their children's learning. Additionally, the large workforce in our country, especially the one that starts with higher educational studies, which are interrupted by the need of assured job, in addition to the lack of experience and restrictions of time for the desirable pace of study; lead university students to take jobs that do not contribute in anything they learn in the classrooms. That's where our project is heading, to give the necessary experience in order to obtain that those students achieve to put into practice their knowledge. This project aims to analyze the feasibility of offering the service of control of homework as a business, providing new working places for university students to enable them to develop their skills through overseeing tasks of children 6 to 11 years, in order them to improve their school performance and support them to develop good study habits